FINANCIAL STATEMENT FRAUD AND ITS DETERMINANTS: EVIDENCE FROM THE FRAUD HEXAGON MODEL IN INDONESIAN MINING COMPANIES (Jurnal Akuntansi, 2026)
This study examines the influence of fraud hexagon model factors—stimulus, capability, opportunity, rationalization, and integrity—on financial statement fraud in Indonesian mining companies listed on the Indonesia Stock Exchange (IDX) during 2018–2023. Using purposive sampling, 40 companies were selected, resulting in 240 observations analyzed through panel data regression with Stata 17. The findings reveal that opportunity and integrity significantly affect financial statement fraud, while stimulus, capability, and rationalization have no significant impact. These results highlight that weak internal controls and low managerial integrity increase the likelihood of fraudulent reporting. The study supports the Fraud Diamond Theory and provides practical implications for strengthening internal control and ethical culture to mitigate fraud risk.